Incorporating grain legumes in cereal-based cropping systems to improve profitability in southern New South Wales, Australia. (June 2017) - Xing, Hongtao; Liu, De Li; Li, Guangdi; Wang, Bin; Anwar, Muhuddin Rajin; Crean, Jason; Lines-Kelly, Rebecca; Yu, Qiang
Abstract: Grain legumes, such as lupins and field peas, are one of key rotation components in Australian agricultural systems, supplying nitrogen (N) to following crops, and potentially increasing farm profitability. In this study, we used a modelling approach to investigate the profitability of incorporating field pea ( Pisum sativum ) and narrowleaf lupin ( Lupinus angustifolius ) in cereal-based (wheat/canola) cropping systems in southern New South Wales (NSW), Australia. We calibrated and validated the Agricultural Production Systems sIMulator (APSIM) with three-year's experimental data to predict yields of field pea and lupin, and N contribution of grain legumes in cereal-based (wheat/canola) crop rotations. We conducted a gross margin analysis to analyse the profitability of adding grain legumes into cereal-based crop rotations at both crop and rotation levels. The simulated results showed that field pea and lupin could contribute 30–65 kg N ha − 1 to the next crop and 60–110 kg N ha − 1 to subsequent crops (wheat/canola) for two years, corresponding to 30–55% and 60–86% of net N inputs of legume-fixed N, respectively. This greatly increased the yields and profitability of wheat/canola in the following two years. Including grain legumes in cereal-based crop rotations was more profitable than non-legume crop rotations, even though the grain legumes were less profitable than wheat/canola in the year of growing. However, N and economic benefits would be reduced to zero if N fertilizer applied to wheat/canola was over the optimal level, i.e. 100–125 kg N ha − 1 in terms of N benefit, or 75 kg N ha − 1 for farm-economic profit. In general, incorporation of grain legumes into cereal-based crop rotations offers an obvious N benefit to subsequent crops and provides an economic benefit for farmers (reduced N applications). This suggests that the contribution of grain legumes to cereal-based cropping systems should be assessed as part of a rotation rather than as a stand-alone crop. Highlights: Calibrated APSIM closely simulated the crop growth, N2 fixation and N concentrations of legumes. Field pea and lupin contributed up to 60–110 kg N ha − 1 to subsequent crops over two years. Incorporating legumes increased farm-economic profit at rotation level. The full benefit of legumes should be evaluated at rotation level rather than at crop level.